The Role of Ustaz and Ustazah in Student Character Building at Muhammadiyah Boarding School Jazaul Ihsan Jombang - Rohmaniyah, Rosa Fajriyatur; Widyaswari, Monica (The Kalimantan Social Studies Journal, 2026)
This study examines the role of ustaz and ustazah in the transfer of learning for student character building in Islamic boarding schools (pesantren). While previous studies have predominantly focused on the outcomes of character education, limited research has investigated how the transfer of learning functions as a mechanism for internalizing values in students’ daily lives. This study addresses this gap by analyzing how educators facilitate the transformation of knowledge into behavior. A qualitative case study approach was employed, with data collected through in-depth interviews, participant observation, and documentation at Muhammadiyah Boarding School Jazaul Ihsan Jombang. The informants consisted of ustaz, ustazah, students, boarding school supervisors, and alumni, who were selected using purposive sampling. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and drawing a conclusion. The findings indicate that ustaz and ustazah play central roles as designers, implementers, and evaluators of character education. Character values such as sincerity, honesty, discipline, and responsibility are systematically integrated into lesson planning, daily routines, and institutional programs. The transfer of learning is implemented through contextual teaching, habituation, role modeling, and continuous mentoring, supported by structured evaluation systems. As a result, students demonstrate observable improvements in spiritual discipline, social skills, independence, and moral behavior. This study contributes to the literature by highlighting the transfer of learning as a key process linking instructional practices and character outcomes, emphasizing that effective character formation requires the consistent integration of cognitive learning and lived experiences within a 24-hour educational environment.